Perlindungan Konsumen Atas Hak Informasi Produk Endorsement Oleh Influencer Atau Selebgram Melalui Media Sosial - Putri Aprilia Mochtar; Rory Jeff Akyuwen; Muchtar Anshary Hamid Labetubun (LUTUR Law Journal, 2024)
A trending advertising method is utilizing influencers on the Instagram platform, or often referred to as "celebrities". This concept is known as endorsement. It cannot be denied that currently there is a lot of illegal skincare and cosmetics circulating in society. There are even some illegal products that are promoted by influencers on social media platforms, where consumers are at risk of experiencing side effects due to the use of these products. Of course, this is contrary to the consumer protection law, Article 17 of the UUPK prohibits business actors from creating advertisements that mislead consumers about the quantity and quality of goods, and even the risks associated with their use. This research aims to find out how consumers are legally protected against endorsement product information promoted by celebs via social media. The research method used is normative juridical, using a statutory approach and a conceptual approach, the legal materials used are primary, secondary and tertiary. Collecting legal materials using literature study, and then analyzing them using qualitative analysis techniques. The results of this research show that legal protection for consumers, if there are consumers who suffer losses caused by business actors, legal regulations have provided a way for consumers to fight for their rights, legal protection for consumers is divided into two, namely preventive (preventing violations) and Repressive (which is the final stage) where business actors who are product endorsers or are endorsed influencers who carry out promotions and create advertising content through social media, have responsibilities based on the UUPK, Civil Code and Health Law. However, this requires the awareness of every consumer to actively defend their rights so that these are not violated by business actors who commit fraud when selling their products via online media.